1990
DOI: 10.1007/bf00030070
|View full text |Cite
|
Sign up to set email alerts
|

The physiological significance of photosystem II heterogeneity in chloroplasts

Abstract: Photosystem II in green plant chloroplasts displays heterogeneity both in the composition of its light-harvesting antenna and in the ability to reduce the plastoquinone pool. These two features are discussed in terms of chloroplast development and in view of a proposed photosystem II repair cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
73
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(82 citation statements)
references
References 18 publications
8
73
1
Order By: Relevance
“…Also in agreement with earlier studies (9,27), we found that photoinhibition adversely affected PSII,, whereas PSIIp appeared resistant to damage (Fig. 4) (17,18). A schematic depicting the role of this activation in the general PSII repair cycle is given in Figure 9.…”
Section: Discussionsupporting
confidence: 79%
“…Also in agreement with earlier studies (9,27), we found that photoinhibition adversely affected PSII,, whereas PSIIp appeared resistant to damage (Fig. 4) (17,18). A schematic depicting the role of this activation in the general PSII repair cycle is given in Figure 9.…”
Section: Discussionsupporting
confidence: 79%
“…As PSII in unstacked regions of the plant thylakoid may correspond to photosystems that are undergoing repair [33,34], the interchange between monomeric and dimeric PSII complexes in the membrane indeed may be rapid. However, if there are nascent PSII components that are stable in the membrane for several hours, then the interchange between monomers and dimers might not be that rapid for all PSII proteins.…”
Section: Turnover Of Psii and Psi Proteinsmentioning
confidence: 99%
“…In intact cells of photosynthetic organisms, photoinhibition is a more complex phenomenon than it is in vitro because photodamaged PSII is rapidly repaired. The main feature of the repair process is the replacement of the D1 protein in the photodamaged PSII by newly synthesized D1 and reassembly of active PSII (Guenther and Melis, 1990;Kettunen et al, 1997; for review, see Mattoo et al, 1989;Aro et al, 1993;Andersson and Aro, 2001). Therefore, the extent of photoinhibition in vivo reflects the balance between the light-induced damage (photodamage) to PSII and the repair of the photodamaged PSII.…”
mentioning
confidence: 99%